Discrimination in the Registration of Marriages of Different Religions: Regulation and Practice in Southeast Asia - Wensislaus Parut; M. Ridha Rahmat Putra; Ferdi Yufriadi; Valensius Ngardi; Meisya Anggraini Rizki (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research focuses on discrimination against religious minorities in Indonesia, Malaysia and Brunei Darussalam, three countries with strong religious traditions and legal systems. As a result of this diversity, different religious backgrounds often raise significant legal and social issues when they want to register their marriages, resulting in unpredictable events and difficulties when settling serious matters. This research utilises a qualitative methodology to examine legal texts, court judgements, court decisions, and data from case studies and interviews, which illustrate the complex interaction between religious and sectarian law. Through a comparative analysis of laws in Indonesia, Malaysia and Brunei Darussalam, this study explains how religious and sectarian norms in the legal system impact discriminatory practices. The research findings of legal and administrative challenges faced by interfaith couples, such as denial of marriage registration and the risk of social stigma, suggest a broader tension between religious authorities and state governance. With comprehensive legal reforms that not only address religious issues but also protect the rights of all individuals, and provide valuable insights and recommendations that can be implemented globally by those responsible for the practice of law, particularly in Indonesia, Malaysia and Brunei Darussalam